A description of the personal social and scholastic background of new students first admitted to the Department of Nursing Science at Medunsa in 1986, and their expectations regarding this university - C.F. van Niekerk; I. Treadwell; H.M. de Vetta (AOSIS, 1988)
In the past few years the comprehensive biographical questionnaire completed by all students newly admitted to MEDUNSA at the beginning of the academic year, provided valuable information regarding students of the Department of Nursing Science. The main purpose of this study is to obtain a profile of nursing students, enrolling at Medunsa for the first time, regarding - their demographic data - the sociological, economical and educational tendencies in their homes - their school achievement and - their expectations of Medunsa.